Games: contexto cultural e curricular juvenil - Moita, Filomena Maria Gonçalves da Silva Cordeiro (2006)
The thesis analyses the underlying curriculum in the games, that is, the kowledge production, skills, competence, values, attitudes and behaviours, which are provided by these artifacts, by youngsters who attend game stores (LAN Houses) in the cities of João Pessoa/ Brazil and Lisbon / Portugal. A very intensive dialogue was maintained with authors who reflect on this subject, among them, Greenfield (1988,1996), Turkle (1995/1997), Aarseth (2005), Burnham (1998), Macedo (2005), Lima JR.(2005), Alves (2005) and with two groups of players ( five Brazilian and five Portuguese). With no intention of data generalization, the interviews and the observations accomplished in the LAN Houses were conducted by the case study guidelines (BOGDAN and BIKLEN, 1994), with an outstanding exploratory choice for being actuallly a new study, with the possibility of contributing for a new theory systematization. In this sense, for the critical analysis of the collected data, the investigation was aided by the analysis and interpretation instrument of Grounded Theory s methodological and instrumental procedures as a complement, specially due to its commitment with the theory (STRAUSS and CORBIN, 1990/1998; TURNER, PIDGEON;BLOCKLEY,1991). The research reveals that the games while natural space of leisure or part of an authoritative curriculum, elucidates better the interest areas and learning process of young people.The collected data allowed the identification that the game context provides a learning environment, a craftsmanship , a cultural context here cultural understood as a new technological view which is related to all social scopes where the new goodfellowships and identities are made and remade, respecting pluralities and singularities a curriculum design environment open, autonomous, concerned with the playful aspects, the pleasure, the subjective, the simulation. Once these youngsters are involved by the games and in their relationships with the partners, knowledge takes place. Such characteristics will establish and warrant a new curriculum expression not related to knowledge present in the school curriculum, but with a curriculum within the communication and information technological culture and, in this specific case here researched, the game context. Hence, this research pointed out that this knowledge basis is, in fact, a cultural juvenile curriculum. In this sense, we are convinced to understand in a much amplified spectrum of the education process and the games itself. Its logic and attractive motivation should be understood as an innovation possibility, a way to ballast the ample and large space of study for youth education process